Efficiency of Polyphenol Extraction from Artificial Honey Using C18 Cartridges and Amberlite„ XAD-2 Resin: A Comparative Study - Chua, Yung An; Hossain, Md. Murad; Alam, Fahmida; Islam, Md. Asiful; Khalil, Md. Ibrahim; Alam, Nadia; Siew, Hua Gan (Hindawi Publishing Corporation, 2016)
A comparative study of the extraction efficiency of nine known polyphenols [phenolic acids (benzoic acid, dihydroxybenzoic acid, gallic acid, trans-cinnamic acid, and vanillic acid) and flavonoids (naringenin, naringin, quercetin, and rutin)] was conducted by deliberately adding the polyphenols to an artificial honey solution and performing solid phase extraction (SPE). Two SPE methods were compared: one using Amberlite XAD-2 resin and another one using a C18 cartridge. A gradient high performance liquid chromatography system with an RP18 column and photodiode array detector was utilized to analyze the extracted polyphenols. The mean percent of recovery from the C18 cartridges was 74.2%, while that from the Amberlite XAD-2 resin was 43.7%. The recoveries of vanillic acid, naringin, and rutin were excellent (>90%); however, gallic acid was not obtained when C18 cartridges were used. Additionally, the reusability of Amberlite XAD-2 resin was investigated, revealing that the mean recovery of polyphenols decreased from 43.7% (1st extraction) to 29.3% (3rd extraction). It was concluded that although Amberlite XAD-2 resin yielded a higher number of compounds, C18 cartridges gave a better extraction recovery. The lower recovery seen for the Amberlite XAD-2 resin also cannot be compensated by repeated extractions due to the gradual decrease of extraction recovery when reused.